Cuidar do outro e de si: análise da sobrecarga do cuidador informal de crianças com deficiência - Oliveira, Camila Martins de (2021)
The arrival of a child with a disability in the family causes adaptations in the family routine, associated with the increase in daily demands that caregivers dedicate to these children, which can trigger conflicts between family relationships, causing changes in plans and perspectives due to the new family context. The family caregiver is considered an informal caregiver, that is, the person in charge of helping with the basic needs of the individual's daily life, during most of the day, without receiving remuneration for this function. This new role is experienced through a multiplicity of needs and feelings, often contradictory and antagonistic by the tension, competence and associated conflict, although aware of the complex and unique character of the family care experience. This study aimed to analyze the burden of informal caregivers of children with disabilities. This is an exploratory and descriptive study of a qualitative nature carried out during the period from September 2018 to July 2019. The participants were 33 informal caregivers of children with disabilities who attended the Associação de Pais e Amigos dos Excepcionais (APAE) in the city of São Paulo. Sobral, Ceara, Brazil. The collection of information was carried out through a socioeconomic form and semi-structured interviews. The content analysis proposed by Bardin was performed using the thematic categorization technique. The study complied with ethical principles according to Resolution 466/2012 of the National Health Council and was approved by the Research Ethics Committee under number 2,806,799. There is a predominance of females 97% (n=32) as informal caregivers, prevalence of the mother as caregiver, dominant age group from 31 to 40 years old 46% (n=15), complete high school 55% (n=18 ), marital status married 52% (n=18), predominant monthly family income of a minimum wage 58% (n=19). The interviews were organized into 3 thematic axes. In Thematic Axis 1 - Emotional overload of the informal caregiver of children with disabilities, the final category, Feeling the care of the other and of oneself: expression, adaptation and memories of the informal caregiver of children with disabilities emerged. In Thematic Axis 2 - Social burden of informal caregivers of children with disabilities: from rights to prejudices experienced in the social context, the final category emerged, Caring for others in the social context: rights, support network, inclusive development, prejudices and stigma. In Thematic Axis 3 - Physical overload of the informal caregiver of children with disabilities: adaptation to the child's daily life needs, the final category Adapting to the11 care of the other emerged: physical overload of the informal caregiver of children with disabilities. Informal caregivers need to be considered beyond support for children with disabilities, identifying their needs, specific problems and essentially their burden, resulting from the care process. It is noteworthy that the knowledge and recognition of the burden to which informal caregivers of children with disabilities are exposed is fundamental for the establishment of strategies to cope with the burdens, for the creation and strengthening of public policies aimed at this public in order to maintain interactions in healthy physical, emotional and social spheres.